Some anatomical variation of paranasal sinuses using sinus endoscopic approach on "cadaver" in Isfahan, Iran - Nezamoddin Berjis; Seyyed Mostafa Hashemi; Mehrdad Rogha; Maryam Abdollahi Biron; Mehrdad Setareh (Advanced Biomedical Research, 2014)
Background: Due to the anatomical variations of the paranasal sinuses and its great importance in sinus surgery, as this area is in very close proximity to vital structures including the optic nerve, carotid artery, and skull base, anatomical knowledge of this area is of high importance. The purpose of this study is defining a full and clear impression of paranasal sinus anatomy and its variations as a model for the human population of the country. Materials and Methods: This study was conducted on 45 cadavers in Isfahan forensic Medicine center during 2010 to 2011. Nasal and paranasal sinuses endoscopic dissection was done with (zero and 30 o ) lenses (Olympus). The methods of performed dissection were via the Stamberger technique. Results: This study showed that 88.9% (40 cases) of middle turbinates were in a typical form, while 6.7% (3 cases) were in medial and only 4.4% (2 cases) were in the lateral form. We also observed 88.9% (40 cases) with Agger nasi cells, 37.8% (17 cases) with Onodi cells, 28.9% cases with accessory Ostia of maxillary sinus (13 cases), and 15.6% of the cases (7 cases) with concha bullosa. The position of the maxillary sinus ostium was as follows. The inferior 1/3 of hiatus semilunaris in 38 (84.5%), superior 1/3 of hiatus semilunaris in 4 (4.4%), middle 1/3 of hiatus semilunaris in 5 (11.1%). The sphenoid ostia in 53.3% (24 cases) were slit shape, 28.9% (13 cases) oval, and 17.8% (18 cases) were round shape. Conclusion : Our survey showed that the distance between anterior nasal spine and anterior wall of the sphenoid sinus was within 7.6 ± 0.2 cm SD.